2018
DOI: 10.1016/j.agee.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Importance of cover crops in alleviating negative effects of reduced soil tillage and promoting soil fertility in a winter wheat cropping system

Abstract: A B S T R A C TReduction of soil tillage is of paramount importance for agricultural soil preservation. However, it is often accompanied by yield reduction and weed management problems. In this perspective, cover crops could play an important role to alleviate weed infestation and sustain yield. In this study, the results from a three-year experiment of cover crop cultivation in different soil tillage treatments is presented, together with results from DayCent simulations on the long term evolution of soil org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 40 publications
(58 reference statements)
8
42
0
3
Order By: Relevance
“…The higher vegetative growth of the leguminous cover crop plots over those in the control may be due to fixing nitrogen in the soil and decomposition of the biomass of the leguminous crops (Kintomo et al, 2008). This study is in agreement with a previous study in which cover crop, pea, produced sufficient biomass and nitrogen availability and led to higher yield of the succeeding crop which was maize (Buchi et al, 2018). Similarly, some earlier studies also reported the beneficial effects of cover crops on improving soil fertility and quality (Porpavai et al, 2006, Abdohalli and Munkholm, 2014, Mitchell et al, 2017.…”
Section: Yieldsupporting
confidence: 91%
“…The higher vegetative growth of the leguminous cover crop plots over those in the control may be due to fixing nitrogen in the soil and decomposition of the biomass of the leguminous crops (Kintomo et al, 2008). This study is in agreement with a previous study in which cover crop, pea, produced sufficient biomass and nitrogen availability and led to higher yield of the succeeding crop which was maize (Buchi et al, 2018). Similarly, some earlier studies also reported the beneficial effects of cover crops on improving soil fertility and quality (Porpavai et al, 2006, Abdohalli and Munkholm, 2014, Mitchell et al, 2017.…”
Section: Yieldsupporting
confidence: 91%
“…That is, farmers experience cost savings, enhanced soil or yield benefits, or higher profits when some practices are adopted in bundles. For example, crop rotations and CCs practices can help manage weeds in no-tillage systems and enhance the benefits from the practice (Büchi, Wendling, Amossé, Necpalova, & Charles, 2018;Triplett & Dick, 2008). Although we are not able to test for profit gains or cost savings from adopting these practices (see Perry et al, 2016), given the dynamics surrounding the adoption of these practices, we believe our results suggest that these practices are seen as complements in adoption by producers.…”
Section: Complementarity In the Adoption Of Conservation Practicesmentioning
confidence: 99%
“…Silva, Muraoka, Guimarães, and Buzetti (2006), researching cover crops in the Cerrado, found that plants that accumulated the greatest dry mass also accumulated a larger amount of K (sunn hemp < millet < fallow). Cover crops accumulate large amounts of nutrients, avoiding loss by leaching (Büchi, Wendling, Amossé, Necpalova, & Charles, 2018); therefore, cover crops that accumulate a larger amount of K may promote lower nutrient loss in the soil profile.…”
Section: Accumulation Of Dry Mass and Nutrients In Cover Cropsmentioning
confidence: 99%